2023
DOI: 10.3390/su15075662
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Self-Efficacy as Mediators between Internal Locus of Control and Adolescents’ Physical Activity

Abstract: In China, the physical activity of adolescents is declining nowadays, which may be linked to their health locus of control, social support, and self-efficacy. The current study has investigated the role of health locus of control, social support, and self-efficacy in adolescents’ physical activity. Using convenient sampling, 569 (18–21 years old) adolescents were surveyed. There were 313 (55.01%) females and 256 (44.99%) males. Data were collected through questionnaires on the study variables. The results disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Compared with numerous studies about environmental factors, few studies focused on internal and social support factors. Yikeranmu et al found that both self-efficacy and social support are positively related to physical activity of adolescents aged 18-21 years old in the city of Xi'an [46]. To our knowledge, no previous study specifically focused on the effect of social support on rural older people's physical activity in China.…”
Section: Physical Activity Is Important To Maintain Physical and Ment...mentioning
confidence: 93%
“…Compared with numerous studies about environmental factors, few studies focused on internal and social support factors. Yikeranmu et al found that both self-efficacy and social support are positively related to physical activity of adolescents aged 18-21 years old in the city of Xi'an [46]. To our knowledge, no previous study specifically focused on the effect of social support on rural older people's physical activity in China.…”
Section: Physical Activity Is Important To Maintain Physical and Ment...mentioning
confidence: 93%
“…Physical exercise can enhance the body's tolerance, reduce the self-loss from fatigue, and improve its self-control ability (Chan et al, 2013). The findings of Yiming et al (2023) suggest that physical exercise can reduce people's level of ego depletion and help reduce their negative effects such as inferiority feeling and depression. Thus, ego depletion may be an important bridge for physical exercise to influence inferiority feeling in children and adolescents with disabilities.…”
Section: Formulation Of Research Hypothesesmentioning
confidence: 99%